2014
DOI: 10.1128/aem.01330-14
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcriptional Control To Increase Titers of Secreted Heterologous Proteins by the Type III Secretion System

Abstract: The type III secretion system (T3SS) encoded at the Salmonella pathogenicity island 1 (SPI-1) locus secretes protein directly from the cytosol to the culture media in a concerted, one-step process, bypassing the periplasm. While this approach is attractive for heterologous protein production, product titers are too low for many applications. In addition, the expression of the SPI-1 gene cluster is subject to native regulation, which requires culturing conditions that are not ideal for high-density growth. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…No cofactors are required for activity [14]. We previously reported that the enzyme beta-lactamase adopts a catalytically active conformation after secretion by the T3SS [6]. We confirmed that beta-lactamase was indeed active in the extracellular space after secretion by the T3SS, and found that enzymatic activity in the extracellular space was both enzyme- and secretion-dependent (Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…No cofactors are required for activity [14]. We previously reported that the enzyme beta-lactamase adopts a catalytically active conformation after secretion by the T3SS [6]. We confirmed that beta-lactamase was indeed active in the extracellular space after secretion by the T3SS, and found that enzymatic activity in the extracellular space was both enzyme- and secretion-dependent (Fig.…”
Section: Resultssupporting
confidence: 81%
“…In addition, the same kinetic parameters were calculated for secreted enzyme (Table 1). This analysis was first performed in standard production media (Lysogeny Broth, Lennox; 5 g L −1 NaCl) [6]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to the well-studied T3S-associated "classical" N-terminal secretion signals, we identified a C-terminal secretion signal that mediates secretion of both endogenous and exogenous proteins. The ability of T3SS to export proteins directly from the bacterial cytoplasm into the extracellular medium or into the host cell cytosol has been exploited for heterologous protein production or antigen delivery during vaccination (46,47). In this context, the newly identified C-terminal T3S signal may have interesting biotechnological applications for production of proteins with N-terminal region that cannot be modified without affecting the protein functionality.…”
Section: Discussionmentioning
confidence: 99%
“…A major level of control of the expression of the SPI-1 and SPI-2 T3SS genes is via the activity of transcriptional regulators, and these regulators can be used to vary the level of SPI-1 and SPI-2 gene expression under various conditions Garmendia et al 2003;Ellermeier and Slauch 2007;Fass and Groisman 2009;Metcalf et al 2014). The expression of SPI-1 and SPI-2 genes from their normal chromosomal locations in the S. Typhimurium genome requires the hilA and ssrAB genes, respectively (Bajaj et al 1995;Ochman et al 1996;Deiwick et al 1999;Garmendia et al 2003;Ellermeier and Slauch 2007;Fass and Groisman 2009).…”
Section: The Role Of Key Transcriptional Regulators In Cloned Spi-1 Amentioning
confidence: 99%